Providing subtitles for Malaysian youtuber / Aisya Aliya Maon and Juritah Misman - Maon, Aisya Aliya; Misman, Juritah (Academy of Language Studies, 2023)
YouTube has become one of the most downloaded video applications in this era. Some users use the application to watch videos, while others use the platform to generate income. However, viewers face some limitations when watching YouTube videos. One of the limitations is the lack of subtitle provision. Creating a service for adding subtitles to Malaysian YouTube content is a need. A survey was carried out in the form of a questionnaire using the Google Form platform. Findings revealed that there was a lack of subtitle provision of the videos uploaded on YouTube and that adding subtitles would be beneficial. Essentially, this study aims to provide English subtitles to one Malaysian YouTuber’s video which was initially done in Malay. Ultimately, this paper looks at the perceptions on why YouTube content creators need subtitles for their videos. It is hoped that this study could contribute towards the effort to provide subtitling work for Malaysian content on the YouTube platform.